"أثر التدريب وفعاليته في التخطيط الاستراتيجي للموارد البشرية" دراسة تطبيقية على مصرف الجمهورية - فروع طرابلس - ليبيا (Comprehensive Journal of Science, 2025)
This study aimed to analyze the impact of training program effectiveness on enhancing strategic human resource planning at Al-Jumhouria Bank – Tripoli branches. The study employed a case study methodology and a descriptive-analytical approach. Primary data was collected through a questionnaire distributed to a random sample of 60 individuals holding various positions across the bank's Tripoli branches. The results demonstrated a statistically significant positive impact of training effectiveness on the quality of strategic human resource planning, with a correlation coefficient of 0.78 and a significance level of 0.000. Furthermore, regression analysis revealed that training effectiveness explained 60.8% of the variance in effective strategic planning. The study concluded that strategic and systematic investment in human resource training is a pivotal factor in achieving competitive advantage and improving banking performance
Keywords: Training, Strategic Planning, Human Resources, Al-Jumhouria Bank, Libya .